PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BADES LEARNING UNTUK MENINGKATKANN KREATIVITAS SISWA DALAM PEMBELAJARAN SEJARAH - Khoirunisa, Azizzah; Putri, Corry Ananda Eka (Sindoro: Cendikia Pendidikan, 2024)
This article examines the use of the Problem-Based Learning (PBL) instructional model to enhance students' creativity in history learning. PBL is a student-centered approach that exposes them to authentic problems to be solved collaboratively. Through an analysis of various previous studies, this article demonstrates that PBL is effective in improving students' critical thinking skills, creativity, learning motivation, and learning outcomes in history subjects. Challenges such as rote learning habits, teacher-centered teaching methods, and limited facilities are also discussed. It is concluded that PBL is an innovative approach that can facilitate students' creativity and 21st-century skills in studying history.